2015
DOI: 10.1017/jfm.2015.131
|View full text |Cite
|
Sign up to set email alerts
|

An analytical consideration of steady-state forced convection within a nanofluid-saturated metal foam

Abstract: An analytical consideration has been made to explore the velocity, temperature and nanoparticle distributions and heat transfer characteristics associated with thermal dispersion and nanoparticle mechanical dispersion within a nanofluid-saturated homogeneous metal foam. A volume-averaging theory was rigorously applied to integrate locally a set of governing equations based on the modified Buongiorno model at the pore scale. Thus, a macroscopic set of volume-averaged governing equations were derived allowing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…In this study, only transverse thermal dispersion conductivity is needed since the flow is thermally and hydro-dynamically fully developed. The corre-lation suggested by Zhang et al [34] is used in this study. As can be seen, the dispersion thermal conductivity depends on the pore-based Reynolds number and porosity.…”
Section: 𝑑 𝑝 = 𝑃𝑃𝐼mentioning
confidence: 99%
“…In this study, only transverse thermal dispersion conductivity is needed since the flow is thermally and hydro-dynamically fully developed. The corre-lation suggested by Zhang et al [34] is used in this study. As can be seen, the dispersion thermal conductivity depends on the pore-based Reynolds number and porosity.…”
Section: 𝑑 𝑝 = 𝑃𝑃𝐼mentioning
confidence: 99%
“…The obtained results of longitudinal thermal dispersion by using Eq. ( 23) for 10 and 20 PPI aluminum foams are compared with the correlation of Zhang et al [16] given in Table 2 and shown in Figure 11. To the best of our knowledge, their suggested equation is the only correlation relating to the longitudinal thermal dispersion of the metal foams in literature.…”
Section: Longitudinal Thermal Dispersionmentioning
confidence: 99%
“…Calmidi and Mahajan [13] suggested a correlation in terms of permeability based Re number while the correlation suggested by Vijay et al [9] is based on channel Re number. Furthermore, Zhang et al [16] used conduit model and suggested a correlation both for longitudinal and transverse thermal dispersion for metal foams. They derived their correlations for thermal dispersion by using the correlation of Calmidi and Mahajan [13] suggested for the interfacial heat transfer coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Ghahremannezhad and Vafai (2018) presented a comprehensive study using porous substrates in MCHSs to find an optimized design, which improves thermal and hydraulic performance of conventional microchannels. Zhang et al (2015) analytically study the fully-developed forced convective heat transfer in a parallel-plate channel, which is filled with porous medium by considering the thermal dispersion and particle mechanical dispersion.…”
Section: Introductionmentioning
confidence: 99%